NILAI KOMUNITARIAN TRADISI REBU SUKU KARO: ALTERNATIF PENGEMBANGAN PENDIDIKAN KEWARGANEGARAAN BERBASIS BUDAYA LOKAL - Oksari Sihaloho; Eshaulin Br. Sembiring; Budi Ali Mukmin (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Satya Wacana, 2026)
Civic Education in Indonesia faces a challenge in integrating communitarian values that are contextual and grounded in the social realities of its communities. Academic studies that empirically explore communitarian values embedded in local wisdom as an alternative source for Civic Education development remain scarce. This article aims to analyze the communitarian values contained in the Rebu tradition of the Karo ethnic group as an alternative for developing local culture-based Civic Education. The study employed a descriptive qualitative approach, collecting data through observation, in-depth interviews, and documentation with seven subjects in Beganding Village, Karo Regency. Data were analyzed using Miles and Huberman's interactive model with technique triangulation to ensure the validity of findings. Results show that the Rebu tradition empirically embodies all five of Etzioni's communitarian values: common good is manifested through the nabei sanction system; sense of community is built through intergenerational value transmission; social responsibility is formed through the internalization of self-regulation norms; respect for tradition exists as dynamic value adaptation; and balance of rights and responsibilities is negotiated collectively. These findings contribute to all three pillars of civic competence simultaneously and offer a concrete model for the substantive not merely decorative but integration of local wisdom into Civic Education.